2023
DOI: 10.32471/exp-oncology.2312-8852.vol-41-no-2.13249
|View full text |Cite
|
Sign up to set email alerts
|

The impact of maximal strength training on quality of life among women with breast cancer undergoing treatment

Abstract: Summary. Cancer rehabilitation programs mainly involve endurance training while little attention has been paid to strength training. Breast cancer (BC) patients lose muscle strength while undergoing adjuvant treatment, thus affecting daily activities and quality of life. Maximal strength training, with an emphasis on velocity in the concentric phase, improves maximal strength and muscle force development characteristics. However, the effect of maximal strength training on quality of life for BC patients underg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 28 publications
1
39
0
Order By: Relevance
“…In similar studies, an increase in the muscle strength of WSBC was found after 12 weeks of high-intensity resistance exercise (Cešeiko et al, 2019;Santagnello et al, 2020). Similar results were observed in elderly survivors of BC who performed 16 weeks of resistance exercise at a high intensity (Serra et al, 2018).…”
Section: Specific Outcomessupporting
confidence: 74%
See 1 more Smart Citation
“…In similar studies, an increase in the muscle strength of WSBC was found after 12 weeks of high-intensity resistance exercise (Cešeiko et al, 2019;Santagnello et al, 2020). Similar results were observed in elderly survivors of BC who performed 16 weeks of resistance exercise at a high intensity (Serra et al, 2018).…”
Section: Specific Outcomessupporting
confidence: 74%
“…Moderate to high-intensity resistance exercises were also used as an intervention (Steindorf et al, 2014;Hagstrom et al, 2015;Cešeiko et al, 2019). Additionally, two types of interventions based on resistance exercises were implemented, which differed only in terms of the intensity (low and high); they were compared with each other, and the intensity was inversely proportionally related to the number of repetitions (Cormie et al, 2013).…”
Section: Duration and Types Of Training That Have To Affect Wsbcmentioning
confidence: 99%
“…This can be a result of the tumour itself, 18 a feature of muscle abnormality, 19 an outcome of the treatment prescribed 20 or a consequence of cancer‐related fatigue 21 . It can also be a result of ageing, malnutrition and a lack of physical activity 19,22,23 . Muscle strength as a nutritional parameter is increasingly being used in intervention studies 24 and as a predictor of mortality 25 .…”
Section: Introductionmentioning
confidence: 99%
“…21 It can also be a result of ageing, malnutrition and a lack of physical activity. 19,22,23 Muscle strength as a nutritional parameter is increasingly being used in intervention studies 24 and as a predictor of mortality. 25 In advanced cancer patients (n = 203) a low handgrip strength (HGS) has been associated with a lower body mass index (BMI), a greater occurrence of sarcopenia and a lower QOL as measured by the McGill Questionnaire.…”
Section: Introductionmentioning
confidence: 99%
“…Oncoplastic surgery is the primary treatment for breast cancer, and may be preceded by neoadjuvant chemotherapy and target therapy treatments, and followed by adjuvant radiotherapy, chemotherapy, target therapy or hormone therapy, these treatments are intended to interfere in the progression or prevent breast neoplasm recurrence 1,2. Despite the development of new surgical techniques and the success of adjuvant or neoadjuvant treatments, some consequences are identified and can lead to functional physical impairment in women, affecting the surgery side upper limb, shoulder range of motion, causing muscle weakness, pain, loss of upper limb functionality, decreased proprioception and lymphedema [3][4][5][6][7][8] . These treatment consequences can cause hypomobility of the upper limb, implicating in physical and psychological distress in women's lives, decreasing the performance of daily living activities 9,10. Therefore, investigations of shoulder range of motion, strength, pain, upper limb functionality, and proprioception after breast cancer surgery are essential, considering the possibility of permanent weakness of the muscles from the breast and the shoulder girdle, or temporary weakness of the anterior serratus, as well as other upper limb muscles 11 .…”
Section: Introductionmentioning
confidence: 99%